AI-Assisted Writing Practices of First-Year EFL Students in the Essay Writing Process - Trie Nakita Sabrina (Jurnal Pendidikan dan Sastra Inggris, 2026)
Generative text AI is becoming more common in students’ writing, including in EFL classrooms. This study explored how generative text AI tools shaped the essay writing practices of first-year EFL students across planning, drafting, revising, and editing. The study used qualitative case study design with three first year students and one lecturer as a contextual informant. Data were collected through a screening questionnaire, semi-structured interviews, students’ essay documents, and a lecturer interview. The data were the analyzed descriptively and thematically, and source triangulation was used to support the trustworthiness of the findings. The results show that AI had already become part of the students’ writing process, although each student used it in a different way. AI was most often used for language-related support, especially grammar, vocabulary, sentence structure, and clarity. Still, it was not used only for editing. The students also used it to generate ideas, organize points, and improve the flow of their writing. The study further found that AI-assisted writing was not a single, fixed practice. Some students udes AI mainly as support, while others depended on it more directly when shaping their drafts. However, the findings also show an important tension. AI made writing easier in some ways, but it also raised concerns about dependence, originality, and the development of students’ own voice. In the end, this study suggests that generative text AI does not only affect the final text, but also changes how students move through the wiritng process itself.